A Novel Exon 19 EGFR mutation in a patient with lung adenocarcinoma: A Case Report and Literature Review - Laura Gutiérrez-Sainz; Rocío Rosas-Alonso; Carlos Rodríguez-Antolín; Carmen Rodríguez-Jiménez; Isabel Esteban Rodríguez; Rafael Peláez; Oliver Higuera Gómez; Julia Villamayor; Patricia Cruz-Castellanos; Alberto Peláez-García; Inmaculada Ibáñez de Cáceres; Javier de Castro Carpeño (Current Problems in Cancer: Case Reports)
Non-small-cell lung cancer (NSCLC) exemplifies how biomarker-driven therapies can alter the natural course of a disease. Clinically significant mutations in the epidermal growth factor receptor (EGFR) in NSCLC include a spectrum of substitutions, deletions, and insertions, mainly affecting exons 18 to 21. The most common EGFR mutations involve exon 19 deletions (19del) or the exon 21 L858R substitution, which are typically sensitive to tyrosine kinase inhibitors (TKIs) such as osimertinib. However, 10 % to 20 % of patients harbor uncommon EGFR mutations, which exhibit variable responses to TKIs. Notably, some rare exon 19 mutations are often undetectable by conventional polymerase chain reaction (PCR) assays. In this case report, we describe an NSCLC patient with a novel exon 19 EGFR mutation identified by next-generation sequencing (NGS), which was not detected by commercial PCR assays. The patient experienced a modest response to osimertinib. We also provide a review of the current literature regarding these uncommon EGFR mutations.